2010
DOI: 10.1097/mao.0b013e3181de4662
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salicylate- and Quinine-Induced Tinnitus in Rats

Abstract: Background-Salicylate and quinine have been shown to reliably induce short-term tinnitus when administered at high doses. The present study compared salicylate and quinine induced tinnitus in rats using the gap prepulse inhibition of acoustic startle (GPIAS).Methods-Twenty-four rats were divided into 2 groups; the first group (n=12) was injected with salicylate (300 mg/kg/d), the second (n=12) was treated with quinine orally at a dose of 200 mg/kg/ d. Animals were treated daily for 4 consecutive days. All rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 45 publications
(40 reference statements)
3
49
0
1
Order By: Relevance
“…These results are consistent with previous studies showing that rats with behavioral evidence of tinnitus from either the lever-pressing approach of Brozoski & Bauer (2006), or the polydypsia approach of Lobarinas and Salvi (Yang, 2007) demonstrated a degraded ability to process silent cues using the same GPIAS procedures employed here. Additional recent studies have also demonstrated the use of GPIAS methods for measuring tinnitus to address a variety of experimental questions [e.g., Wang, et al, 2009; Ralli, et al, 2010; Zhang, et al, 2010]. The current study also demonstrates a time of apparent hyperacusis in behavioral responses to prepulse stimuli (Figure 6) for a period of 2–3 weeks following noise exposure, consistent with a hyperexcitable auditory system.…”
Section: Discussionsupporting
confidence: 70%
“…These results are consistent with previous studies showing that rats with behavioral evidence of tinnitus from either the lever-pressing approach of Brozoski & Bauer (2006), or the polydypsia approach of Lobarinas and Salvi (Yang, 2007) demonstrated a degraded ability to process silent cues using the same GPIAS procedures employed here. Additional recent studies have also demonstrated the use of GPIAS methods for measuring tinnitus to address a variety of experimental questions [e.g., Wang, et al, 2009; Ralli, et al, 2010; Zhang, et al, 2010]. The current study also demonstrates a time of apparent hyperacusis in behavioral responses to prepulse stimuli (Figure 6) for a period of 2–3 weeks following noise exposure, consistent with a hyperexcitable auditory system.…”
Section: Discussionsupporting
confidence: 70%
“…Robust DPOAEs were present at all 6 test frequencies (F 2 =6, 8, 12, 16, 24, and 30 kHz respectively) before SS treatment. However, at 2 h post-treatment, DPOAE amplitudes had decreased significantly at low frequencies (2F 1 -F 2 ≤ 10.7 kHz) and high frequencies (2F 1 -F 2 ≥ 20 kHz), whereas little change occurred at the mid-frequencies (2F 1 -F 2 =16 kHz), a frequency region previously associated with the pitch of salicylate-induced tinnitus (Ralli et al, 2010; Yang et al, 2007). The mild reduction in mid-frequency DPOAEs surrounded by large losses at low and high frequencies could alter the tonotopic organization in the CNS as discussed below.…”
Section: Resultsmentioning
confidence: 86%
“…Salicylate causes transient and reversible tinnitus when administered at high doses in both humans (Mongan et al, 1973) and animals (Ralli et al, 2010). Behaviourally, salicylate has been shown to significantly impair gap detection in rats (Turner and Parrish, 2008), consistent with the results shown here.…”
Section: Discussionmentioning
confidence: 99%
“…The development of animal models of tinnitus has played an essential role in furthering our knowledge of the physiological and molecular mechanisms that underlie this condition (Kaltenbach, 2011). The most common trigger for the condition is repeated exposure to excessive loud noise (Eggermont and Roberts, 2004), but among others it can also occur as a result of the effects of ototoxic drugs such as sodium salicylate or quinine (Ralli et al, 2010). Sodium salicylate is frequently the cause of tinnitus when patients receive high doses of aspirin (Cazals, 2000).…”
Section: Introductionmentioning
confidence: 99%